Impact Analysis of midpoint Connected STATCOM on Distance Relay Performance - Ilango R; Sree Renga Raja T (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
This paper presents the impact of the Static Synchronous Compensator (STATCOM) on the performance of distance protection of EHV transmission lines. A 400kV transmission system having midpoint connected STATCOM with its control circuit is modeled using MATLAB/SIMULINK software. The impact of STATCOM on distance relay for different fault conditions and different fault locations is analyzed. Simulation results indicate that the presence of the STATCOM in the transmission system significantly changes the line impedance seen by the distance relay to be lower or higher than the actual line impedance. Due to this the performance of the distance relay changes, either overreaches or under reaches. DOI: http://dx.doi.org/10.11591/telkomnika.v13i2.6987